2021
DOI: 10.1186/s13063-021-05537-6
|View full text |Cite
|
Sign up to set email alerts
|

The future is now: our experience starting a remote clinical trial during the beginning of the COVID-19 pandemic

Abstract: Background The World Health Organization declared the outbreak of SARS-CoV-2 a pandemic on February 11, 2020. This organism causes COVID-19 disease and the rapid rise in cases and geographic spread strained healthcare systems. Clinical research trials were hindered by infection control measures discouraging physical contact and diversion of resources to meet emergent requirements. The need for effective treatment and prevention of COVID-19 prompted an untested investigational response. Trial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The set-up and early implementation of the Coverage trial in the COVID-19 outbreak context involved and/or requisitioned the involvement of a large number of actors from several disciplines, which was perceived as a source of dynamism by interviewees; this has been reported in another study in the USA [ 34 ]. However, while the motivations of young clinicians and GPs to be involved in clinical research, to train on-the-job, and to participate in the Coverage trial implementation was praised by some of the stakeholders interviewed, others questioned whether this lack of prior training and experience has been an obstacle to the implementation of the trial.…”
Section: Discussionmentioning
confidence: 95%
“…The set-up and early implementation of the Coverage trial in the COVID-19 outbreak context involved and/or requisitioned the involvement of a large number of actors from several disciplines, which was perceived as a source of dynamism by interviewees; this has been reported in another study in the USA [ 34 ]. However, while the motivations of young clinicians and GPs to be involved in clinical research, to train on-the-job, and to participate in the Coverage trial implementation was praised by some of the stakeholders interviewed, others questioned whether this lack of prior training and experience has been an obstacle to the implementation of the trial.…”
Section: Discussionmentioning
confidence: 95%
“…Yet another could be use of asynchronous technology using images or data collected at one point in time and responded to later [34]. Further exploration of electronic patient-reported outcomes and shared decisionmaking is warranted, as are remote visit communication barriers and the inability to perform a full clinical exam [35].…”
Section: Discussionmentioning
confidence: 99%
“…We believe the application of telemedicine and some other techniques may be relevant since they minimize and offset some negative effects of the pandemic. A study conducted in the USA demonstrated that telemedicine improved accuracy and timeliness of safety event reporting since it enabled immediate, direct transmission of patients’ personal health data from home to the investigators, allowing a prompt assessment and follow-up treatment decision ( 30 ). In China, WeChat-based telemedicine has been highly recommended for remote follow-up visits during the pandemic ( 31 ).…”
Section: Discussionmentioning
confidence: 99%